Analisis Kualitas Hidup Pada Pasien Hipertensi di Salah Satu Puskesmas di Kota Kupang - Maria Melenia Bobo; Magdarita Riwu; Derri Rizkiyanti Tallo Manafe; Efrisca M. Br. Damanic (Pusat Riset dan Inovasi Nasional, 2025)
Hypertension is a serious health problem. According to data from the World Health Organization for 2021, hypertension is the number one risk factor for death worldwide (10.44 million). Hypertension that is not disabled will affect the decrease in the value of the patient's quality of life. This study aims to determine the relationship between hypertension and the quality of life of hypertensive patients at the Oesapa Health Center in Kupang. This study used an observational analytical research method with a cross sectional approach where in this study data collection was carried out regarding the variables studied at one time only. There is a significant relationship with a strong correlation between hypertension and Physical Health Quality of Life (KHKF) in hypertensive patients with a p=0.021 (r=-0.530) and there is a significant relationship with a weak correlation between hypertension and Mental Health Quality of Life (KHKM) in hypertensive patients with a value of p = 0.017 (r = -0.230). Hypertension has a relationship with quality of life in hypertensive patients at the Oesapa Kupang Health Center.